Formulasi dan Uji Karakteristik Fisik Krim Blush On Dari Sari Kelopak Bunga Rosella (Hibiscus sabdariffa L.) Sebagai Pewarna Alami - Ahlan Sangkal; Hamidah Sri Supriati; Nini M. Hanafi (Jurnal Sains dan Kesehatan, 2020)
Rosella (Hibiscus sabdariffal L.) contains anthocyanins which can be used as natural dyes and at the same time as an antioxidant that functions as an antidote to free radicals. The aim of this research was to formulate and test the physical characteristics of the blush on cream preparation from the essence of Rosella (Hibiscus sabdariffa L.) as a natural dye. This type of research is an experiment in the laboratory. The extract of Rosella calis flower is crushed and the filtrate is taken by extracting it. The extract is made into blush on cream preparations with a concentration of 20%, 40% and 60%. The organoleptic test results of blush on cream on the control were soft textured, white, smelled like cream, soft-textured F1, ivory white, Rosella flower-like smell, soft-textured F2, light cream colored, Roselle flower-like smell, and F3 small granular texture pink color, distinctive smell of Rosella flower, homogeneity test on homogeneous control, homogeneous F1, homogeneous F2, and not homogeneous F3, control pH test values: 6, F1: 6, F2: 6, F3: 4, control spreadability test: 6 , 3 cm, F1: 5.7 cm, F2: 5 cm, F3: 4.5 cm, control adhesion test: 4.42 seconds, F1: 4.21 seconds, F2: 4.19 seconds, F3: 4.12 seconds and emulsion type test on control: M / A, F1: M / A, F2 M / A, F3: M / A. The formulation and physical characteristics test of blush cream from the extract of Rosella flower petals (Hibiscus sabdariffa L.) cannot be formulated as a blush cream preparation and does not have good characteristics, one of which is the exposure to light and heating during the formulation.